DIFERENSIASI PERAN ANGGOTA KELUARGA MISKIN PERKOTAAN: PERSPEKTIF MODAL SOSIAL - Prayitno, Ujianto Singgih (Jurnal Aspirasi, 2013)
This research was conducted within urban poor families. These families are generally bound in a complex,cross cutting, and changing network of relationships, which together would reinforce the existence of society. Economic productivity of poor families is supported by all members of the family, including the children, with a definite division of work. With qualitative-phenomenological approach, the study concluded that the degree of independence of the households is supported by strong family ties, mutual trust among members of the family, sharing value, and the spirit of working together in solving problems. Interaction between families in the community who are also based on the norms of trust, mutual help, and togetherness, is a form of social capital and is important for the formation of social networks.